Genome Replication Is Associated With Release of Immunogenic DNA Waste - Schubert, Nadja; Schumann, Tina; Daum, Elena; Flade, Karolin; Ge, Yan; Hagedorn, Lara; Edelmann, Winfried; Müller, Luise; Schmitz, Marc; Kuut, Gunnar; Hornung, Veit; Behrendt, Rayk; et al. (Frontiers in Immunology, 2022)
Innate DNA sensors detect foreign and endogenous DNA to induce responses to infection and cellular stress or damage. Inappropriate activation by self-DNA triggers severe autoinflammatory conditions, including Aicardi Goutières syndrome (AGS) that can be caused by defects of the cytosolic DNase 3’repair exonuclease 1 (TREX1). TREX1 loss-of-function alleles are also associated with systemic lupus erythematosus (SLE). Chronic activation of innate antiviral immunity in TREX1-deficient cells depends on the DNA sensor cGAS, implying that accumulating TREX1 DNA substrates cause the inflammatory pathology. Retrotransposon-derived cDNAs were shown to activate cGAS in TREX1-deficient neuronal cells. We addressed other endogenous sources of cGAS ligands in cells lacking TREX1. We find that induced loss of TREX1 in primary cells induces a rapid IFN response that requires ongoing proliferation. The inflammatory phenotype of Trex1-/- mice was partially rescued by additional knock out of exonuclease 1, a multifunctional enzyme providing 5’ flap endonuclease activity for Okazaki fragment processing and postreplicative ribonucleotide excision repair. Our data imply genome replication as a source of DNA waste with pathogenic potential that is efficiently degraded by TREX1.